Note on rare snake eels (Anguilliformes: Ophichthidae) and additional data on three Neenchelys recently described from Taiwan - Ho, Hsuan-Ching; Hibino, Yusuke; Huang, Jian-Fu (Zootaxa, 2018)
Three rare snake eel species, Allips concolor McCosker, 1972, Neenchelys daedalus McCosker, 1982, and Apterichtus moseri (Jordan & Snyder, 1901), were newly collected from Taiwan. The distribution ranges of the first two species are now extended to the South China Sea off southern Taiwan and that of the third is extended southward to off northwestern Taiwan. Supplemental data for three recently described species, Neenchelys diaphora, N. gracilis and N. similis, from Taiwan are provided.